2021
DOI: 10.4266/acc.2020.00787
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prognostic scoring system in patients with pneumonia requiring ventilator care for more than 4 days: a single-center observational study

Abstract: Background: The aim of the present study was to develop a prognostic model using demographic characteristics, comorbidities, and clinical variables measured on day 4 of mechanical ventilation (MV) for patients with prolonged acute mechanical ventilation (PAMV; MV for >96 hours). Methods: Data from 437 patients (70.9% male; median age, 68 years) were obtained over a period of 9 years. All patients were diagnosed with pneumonia. Binary logistic regression identified factors predicting mortality at 90 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 24 Various prognostic indicators have been identified, including older age (⩾65 years); underweight (BMI ⩽ 18.5 kg/m 2 ); hemato-oncologic malignancies as comorbidities; the requirement for medical resources such as vasopressors, neuromuscular blockade, and hemodialysis on day 4 of MV; and other clinical variables, such as PaO 2 /FiO 2 < 200 mm Hg, platelet count < 100 × 10 9 /L, albumin < 3.5 g/dL, BUN >7 mmol/L, pH < 7.35, lactic acid > 2.0 mmol/L, and serum sodium ⩾ 145 mmol/L. 26 32 Other extraneous factors, including the perspectives of patients’ families or surrogates, physician–family communications, and the utilization of medical resources, could also be considered prognostic indicators. A model that includes these individualized parameters, rather than the m-NUTRIC score alone, may be more predictive of mortality in patients undergoing PAMV.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Various prognostic indicators have been identified, including older age (⩾65 years); underweight (BMI ⩽ 18.5 kg/m 2 ); hemato-oncologic malignancies as comorbidities; the requirement for medical resources such as vasopressors, neuromuscular blockade, and hemodialysis on day 4 of MV; and other clinical variables, such as PaO 2 /FiO 2 < 200 mm Hg, platelet count < 100 × 10 9 /L, albumin < 3.5 g/dL, BUN >7 mmol/L, pH < 7.35, lactic acid > 2.0 mmol/L, and serum sodium ⩾ 145 mmol/L. 26 32 Other extraneous factors, including the perspectives of patients’ families or surrogates, physician–family communications, and the utilization of medical resources, could also be considered prognostic indicators. A model that includes these individualized parameters, rather than the m-NUTRIC score alone, may be more predictive of mortality in patients undergoing PAMV.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in PaO 2 /FiO 2 ratio between the two patient groups; this value was found not to be a risk factor of PMV. Oh et al reported that the ventilator days in pneumonia was related to PaO 2 /FiO 2 ratio [23]. It has been reported that the PaO 2 /FiO 2 ratio may differ between patients with acute respiratory distress syndrome who survive versus those who do not, although it does not necessarily serve as an indicator of mortality because of variations in MV settings, the patients' condition, and patient posture.…”
Section: Discussionmentioning
confidence: 99%
“…Gattinoni and colleagues’ original equation for MP is based on volume-controlled ventilation with a linear increase in airway pressure and was validated in paralyzed patients [ 5 ]. Thus, this equation may not be useful in a significant number of mechanically ventilated patients because the use of pressure-regulated ventilation has been increasing [ 10 ], and restricted use of neuromuscular blocking agents (NMBAs) is advocated due to their detrimental effects [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%